John Digges account book and account sheets - Digges, John.
Account book (1 volume; 1720-1749) and miscellaneous account sheets (1800-1812). Some of the accounts relate to debts whose bonds were assigned to Charles Carroll.
Merchant and businessman.
Collection material in English.
Keywords: Carroll, Charles, -- 1702-1782.; Business records -- Maryland; Maryland -- Commerce; Businessmen; Merchants